Relationship between nutritional assessment and nutritional risk screening in hospitalized children with cerebral palsy: a single-center prospective study - Jixun Zhao; Yuyang Qiu; Junmeng Su; Huiqun Wang (Scientific Reports)
Abstract Cerebral palsy (CP) strongly affects the growth and development of children and is accompanied by a high risk of malnutrition. This study aims to characterize the nutritional status of hospitalized children with CP, evaluate the efficacy of four nutritional risk screening tools, analyze influencing factors of malnutrition. In our study, 64.8% of all 91 patients were malnourished. Nutritional status was associated with the gross motor function classification system (GMFCS) grade, the manual ability classification system (MACS) grade, caregiver concern, and age (P < 0.05). Compared with Z score, the sensitivity and consistency of the four malnutrition risk screening tools were lower. Multivariate logistic regression analysis revealed that older age, lower albumin (ALB) concentration, and MACS grade II were independent influencing factors for malnutrition. The prediction model with 4 variables, including age, albumin, triglyceride and MACS grade, was included, the AUC (95% CI) was 0.88 (0.81–0.95), and the P value of the H-L goodness-of-fit test was 0.588, which has practical value. We indicate that the rate of malnutrition in hospitalized children with CP remains high and still requires extensive attention from society, especially in clinical nutrition.